Opioid analgesic use after ambulatory surgery: a descriptive prospective cohort study of factors associated with quantities prescribed and consumed - Ziming Xuan; Christopher W Shanahan; Olivia Reding; Inga Holmdahl; Julia Keosaian; David McAneny; Marc Larochelle; Jane Liebschutz (BMJ Open)
Objectives To prospectively characterise: (1) postoperative opioid analgesic prescribing practices; (2) experience of patients undergoing elective ambulatory surgeries and (3) impact of patient risk for medication misuse on postoperative pain management.Design Longitudinal survey of patients 7 days before and 7–14 days after surgery.Setting Academic urban safety-net hospital.Participants 181 participants recruited, 18 surgeons, follow-up data from 149 participants (82% retention); 54% women; mean age: 49 years.Interventions None.Primary and secondary outcome measures Total morphine equivalent dose (MED) prescribed and consumed, percentage of unused opioids.Results Surgeons postoperatively prescribed a mean of 242 total MED per patient, equivalent to 32 oxycodone (5 mg) pills. Participants used a mean of 116 MEDs (48%), equivalent to 18 oxycodone (5 mg) pills (~145 mg of oxycodone remaining per patient). A 10-year increase in patient age was associated with 12 (95% CI (−2.05 to –0.35)) total MED fewer prescribed opioids. Each one-point increase in the preoperative Graded Chronic Pain Scale was associated with an 18 (6.84 to 29.60) total MED increase in opioid consumption, and 5% (−0.09% to –0.005%) fewer unused opioids. Prior opioid prescription was associated with a 55 (5.38 to –104.82) total MED increase in opioid consumption, and 19% (−0.35% to –0.02%) fewer unused opioids. High-risk drug use was associated with 9% (−0.19% to 0.002%) fewer unused opioids. Pain severity in previous 3 months, high-risk alcohol, use and prior opioid prescription were not associated with postoperative prescribing practices.Conclusions Participants with a preoperative history of chronic pain, prior opioid prescription, and high-risk drug use were more likely to consume higher amounts of opioid medications postoperatively. Additionally, surgeons did not incorporate key patient-level factors (eg, substance use, preoperative pain) into opioid prescribing practices. Opportunities to improve postoperative opioid prescribing include system changes among surgical specialties, and patient education and monitoring.